The use of the microalgae Tisochrysis lutea in a green water system increases the weight of seahorse larvae Hippocampus reidi, Ginsburg, 1933 - E.M.O. Sousa; N.Y. Oliveira; I.A. Silva; R.A. Ozório; M.W.S. Cordeiro; R. Wagner; M.Y. Tsuzuki (Arquivo Brasileiro de Medicina Veterinária e Zootecnia)
ABSTRACT The study aimed to investigate the influence of different microalgae used in green water culture on the survival rate, performance and fatty acids profile of H. reidi larvae. The study consisted of four treatments composed of two microalgae (Tisochrysis lutea - ISO and Chaetoceros muelleri-CHO), used alone (TISO and TCHO) or combined (TIC, 1:1) in the culture water, and a treatment without microalgae (TWM) during the first 15 days of culture. The larvae were fed from the first to the seventh day with copepods (Parvocalanus crassirrostris) and rotifers (Brachionus rotundiformis), and from the eighth day onwards, the gradual inclusion of Artemia sp. nauplii. No differences in the survival rates were observed. The addition of specifically T. lutea in the TISO and TIC treatments affected weight, weight gain, specific growth rate and the condition factor, of the larvae compared to TWM. A higher concentration of (PUFA), DHA, ∑ n-3, n-3/n-6 ratio were found in TISO larvae after 15 days of rearing. In conclusion, the addition of microalgae T. lutea proved to be an advantageous alternative in a large-scale production system, since its inclusion affected the performance and the lipid composition of the larvae compared to the TWM.